Judah and the Judeans in the fourth century B.C.E - Lipshits, ʿOded; Knoppers, Gary; Albertz, Rainer (Eisenbrauns, 2010)
The Achaemenid empire in the fourth century B.C.E. : a period of decline? / Josef Wiesehöfer -- The settlement archaeology of the province of Judah : a case study / Oded Lipschits and Oren Tal -- Administration in fourth-century B.C.E. Judah in light of epigraphy and numismatics / André Lemaire -- Yehud stamp impressions in the fourth century B.C.E. : a time of administrative consolidation? / Oded Lipschits and David Vanderhooft -- "And they did note care to speak Yehudit" : on linguistic change in Judah during the late Persian era / Ingo Kottsieper -- Archaeology and Archaiologias : relating excavations to history in fourth-century B.C.E. Palestine / Lester L. Grabbe -- Idumea in the late Persian period (fourth century B.C.E.) / Amos Kloner and Ian Stern -- The onomasticon of Mareshah in the Persian and Hellenistic periods / Esther Eshel -- The dating of the first phase of the Samaritan temple on Mount Gerizim in light of the archaeological evidence / Yitzhak Magen -- Do the earliest Samaritan inscriptions already indicate a parting of the ways? / Bob Becking -- The governors of Samaria in the fifth and fourth centuries B.C.E. / Hanan Eshel -- The late Persian formation of the Torah : observations on Deuteronomy 34 / Konrad Schmid -- The Pentateuch, the prophets, and the Torah in the fifth and fourth centuries B.C.E. / Reinhard Achenbach -- The canonical alignment of the book of Joshua / Rainer Albertz -- Nehemiah and Sanballat : the enemy without or within? / Gary N. Knoppers -- A new model for the composition of Ezra-Nehemiah / Jacob L. Wright -- Who knew what? The construction of the monarchic past in Chronicles and implications for the intellectual setting of Chronicles / Ehud Ben Zvi -- "Those doing the work for the service in the house of the Lord" : 1 Chronicles 23:6-24:31 and the sociohistorical context of the temple of Yahweh in Jerusalem in the late Persian/early Hellenistic period / John W. Wright -- The development of Jewish sectarianism from Nehemiah to the Hasidim / Joseph Blenkinsopp